2017
DOI: 10.1007/s11356-017-0583-0
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessment of instant noodles commonly consumed in Port Harcourt, Nigeria

Abstract: The current study investigated the levels of some heavy metals [lead (Pb), arsenic (As), nickel (Ni), mercury (Hg), copper (Cu), cadmium (Cd), aluminum (Al), and chromium (Cr)] and polycyclic aromatic hydrocarbons (PAHs) in six brands of instant noodles (CFN, GFC, NGP, GAA, CUN, and FCS) commonly consumed in Port Harcourt, Nigeria. Risks of consumption of contaminated noodles were also assessed. Heavy metal content and PAHs were determined using flame atomic absorption spectrophotometer and gas chromatography,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
0
22
2
Order By: Relevance
“…They are classified as probable human carcinogens. However, the result was inconsistent with the findings of Charles and co-workers [27].…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…They are classified as probable human carcinogens. However, the result was inconsistent with the findings of Charles and co-workers [27].…”
Section: Resultscontrasting
confidence: 98%
“…In addition, technical processes (i.e., withering followed by drying) can increase the concentrations of PAHs in tea leaves by more than 200 times [22,26]. Moreover, PAHs have been detected in instant noodles [27]. The production of PAHs in industries was reportedly favoured by an oxygen-deficient flame, temperatures in the range of 650–900 °C, and highly un-oxidized fuels [28].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study analyzing heavy metal contamination in instant noodles revealed exceeding concentrations of Pb in products sold in Nigeria, but showed acceptable levels of As, Hg, and Cd (Charles, Ogbolosingha, & Afia, 2017). Another such study, comparing the heavy metal contamination of instant noodles made in Iran to those that were imported into the country, revealed significantly high concentrations of Pb, Cd, Cr, and Al in Iranian samples (Tajdar-Oranj et al, 2018;Onyema et al, 2014).…”
Section: Impact On Foodmentioning
confidence: 99%
“…However, with the industry's growing demand, there is also increasing awareness about the long-term health effects of such processed foods. Several recent studies conducted in Iran, Nigeria, Bangladesh, and China have found significantly high concentrations of heavy metals in many of the commercially available instant noodle products (Tajdar-Oranj et al, 2018;Charles, Ogbolosingha & Afia, 2017;Jothi & Uddin, 2014;Onyema et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Air, land and water pollution are contributing to https://dx.doi.org/10.4314/ijs.v22i2.14 the presence of these harmful elements in food stuff including instant noodles (Onyema et al, 2014(Onyema et al, , 2016. Food processing equipment, containers, additives and packaging materials are some of the possible channels through which noodles can be contaminated with heavy metals (Jothi and Uddin, 2014, Omuku et al, 2014, Charles et al, 2018. Soil irrigation with contaminated water, fertilizer and pesticides application, industrial emissions, storage container, and road traffic with leaded petrol are some of the possible sources of heavy metals in wheat which serves as the main raw material for noodles production (Gholam and Jahead, 2005;Ihedioha, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%